2016
DOI: 10.1038/srep24345
|View full text |Cite
|
Sign up to set email alerts
|

Increased N6-methyladenosine in Human Sperm RNA as a Risk Factor for Asthenozoospermia

Abstract: Male infertility is a worldwide medical problem. Asthenozoospermia is a common cause of infertility. Epigenetic modifications of DNA and histones have been shown to influence human infertility, but no research has explored whether N6-methyladenosine (m6A) level in RNA is associated with asthenozoospermia. Here, we collected a total of 52 semen samples, including 20 asthenozoospermia patients and 32 healthy controls. An LC-ESI-MS/MS method was used to detect m6A contents in sperm RNA, and real-time PCR was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 37 publications
1
54
0
Order By: Relevance
“…In humans, increased expression of FTO, METTL3 and METTL14 , as well as levels of m 6 A, have been identified in the sperm of infertile men (Yang et al . ), in addition to significant changes in both histone modification and DNA methylation status (Rahiminia et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, increased expression of FTO, METTL3 and METTL14 , as well as levels of m 6 A, have been identified in the sperm of infertile men (Yang et al . ), in addition to significant changes in both histone modification and DNA methylation status (Rahiminia et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…While Alkbh5 null mice are viable and appear anatomically normal, they exhibit impaired fertility due to the apoptosis of meiotic metaphase-stage spermatocytes [39]. A study of human asthenozoospermia patients found a correlation between elevated METTL3 and m 6 A levels, and sperm motility [49]. ALKBH5 localizes to the nucleus, and loss of ALKBH5 impairs mRNA export, RNA metabolism, and assembly of mRNA processing factors in nuclear speckles [39].…”
Section: M6a Is a Dynamic Mrna Modification: The Demethylasesmentioning
confidence: 99%
“…Perturbations of the regulatory machinery of m 6 A modification might be associated with human diseases or cancers. For example, METTL3 and METTL14 increase m 6 A levels of sperm in asthenozoospermia . FTO expression inversely correlates with m 6 A levels during adipogenesis, and ALKBH5 deficiency reduces m 6 A levels and leads to compromised spermatogenesis in mice .…”
mentioning
confidence: 99%